MODEL MANAJEMEN KURSUS GARMEN BERBASIS DUDI PADA PENDIDIKAN KECAKAPAN HIDUP LEMBAGA KURSUS DAN PELATIHAN - Sujanto, Alex (INFOKAM, 2015)
The aim of this study was to produce garment course management model based world of business and industry (WBI) on life skills education courses and training institutions. This study uses a model of R & D Borg and gall, with the following steps: (1) The preliminary study carried out in 4 LKP with the same criteria, namely performers B, and accredited by BAN-PNF (2) a validated design experts through focus group discussions. (3) and test the effectiveness of a hypothetical models. Collecting data through observation, interviews, questionnaires and documentation. Data were analyzed using descriptive qualitative analysis and paired t-test. Based on the results of the study showed that the garment course management model based WBI on the life skills education courses and training institutions can improve the effectiveness of management courses for courses managers and improving the competence of learners. Keywords: garment courses management, based on WBI, life skills education courses, and training institutions.